Intellectual Capital and the Performance of Manufacturing Companies in Indonesia - Rahmat Setiawan; Budi Yuda Prawira (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2018)
This study aimed at examining the effect of intellectual capital and its components covering value added capital employed, value added human capital, and structural capital value added on the firm performance. Intellectual capital was measured by using Pulic’s model, while the firm performance was measured by return on asset, return on equity, and market-to- book ratio. The samples used in this study were 103 manufacturing industries and we also investigated every subsector of the manufacturing industries including 51 basic and chemical industries, 30 miscellaneous industries, and 22 consumer goods industry listed on Indonesia Stock Exchange during the period of 2012 up to 2016. Multiple regression analysis was used to test the hypothesis. The result of the study showed that intellectual capital had a significant positive effect on return on asset, return on equity, and market-to-book intellectual capital on the firm performance in each subsector of the manufacturing industry. Value added capital employed as a component of intellectual capital was the most influential component on the firm performance. This findings indicated that a firm with great and well managed of capital employed, allowing a firm to improve their performance. Penelitian ini bertujuan untuk menguji pengaruh intellectual capital dan komponennya yang meliputi value added capital employed, value added human capital, dan structural capital value added terhadap kinerja perusahaan. Intellectual capital diukur menggunakan model Pulic, sementara kinerja perusahaan diukur dengan return on asset, return on equity, dan market-to-book ratio. Sampel yang digunakan dalam penelitian ini adalah 103 perusahaan pada industri manufaktur, dan kami juga kami meneliti masing-masing subsektor dari industri manufaktur yang meilputi 51 perusahaan pada  industri dasar dan bahan kimia, 30 perusahaan pada aneka indstri, dan 22 perusahaan pada industri barang konsumsi yang terdaftar di Bursa Efek Indonesia selama jangka waktu 2012-2016. Analisis regresi berganda digunakan untuk menguji hipotesis. Hasil penelitian menunjukkan bahwa intellectual capital berpengaruh positif signifikan terhadap return on asset, return on equity, dan market-to-book ratio di semua industri. Selain itu, hasil penelitian ini juga menunjukkan bahwa tidak ada perbedaan pengaruh intellectual capital terhadap kinerja perusahaan pada masing-masing subsektor industri manufaktur. Value added capital employed yang merupakan komponen dari intellectual capital merupakan komponen yang paling berpengaruh terhadap kinerja perusahaan. Temuan ini menunjukkan bahwa perusahaan dengan modal yang besar dan dikelola dengan baik, memungkinkan perusahaan untuk meningkatkan kinerjanya.Intellectual capital, value added capital employed, value added human capital, structural capital value added, return on asset, return on equity, market-to-book ratio.